2016
DOI: 10.1007/s00421-016-3400-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in boys and men exercising at the same heat production per unit body mass

Abstract: Boys and men demonstrated similar thermoregulatory responses to 80 min of exercise in the heat performed at a fixed [Formula: see text] per unit BM. Sweat volume was lower in boys compared to men, despite similarities in absolute [Formula: see text] and E req.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…The same metabolic heat production, rather than %V O 2peak or maximal power output, was used to match exercise intensity to induce the same thermoregulatory responses. The use of exercise intensity based on metabolic heat production normalized to body mass can provide an unbiased comparison of thermoregulatory responses (i.e., ⌬T re ) in heterogeneous groups, such as children and adults (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same metabolic heat production, rather than %V O 2peak or maximal power output, was used to match exercise intensity to induce the same thermoregulatory responses. The use of exercise intensity based on metabolic heat production normalized to body mass can provide an unbiased comparison of thermoregulatory responses (i.e., ⌬T re ) in heterogeneous groups, such as children and adults (17).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most comparisons of children and adults exercising in the heat have employed similar relative exercise intensities (%V O 2peak ) (2, 13) and have not considered the impact of differential metabolic heat production. A recent study (17) suggested that exercise prescribed to elicit a fixed metabolic heat production per unit body mass guaranteed similar thermoregulatory responses between boys and men exercising in the heat.…”
mentioning
confidence: 99%
“…Because the heat storage capacity of any structure is determined by its mass and thermal properties, exercise performed at a mass-specific metabolic heat production rate (W·kg −1 ) has recently been used to evaluate thermoregulatory function in children and adults ( 53 ). However, as noted above, mass-specific normalization (ratiometric scaling) will only fully account for differences in body size when the least-squares, linear regression relationship between that variable and body mass displays a zero y -intercept.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…To our knowledge, only one other direct child–adult comparison of exercise thermoregulation exists ( 53 ). In that research, children and adults with similar mass-specific V˙O 2peak were assessed during intermittent exercise in hot, dry conditions.…”
Section: Child–adult Comparisons During Exercise-heat Stressmentioning
confidence: 99%
“…Stage 1 of biological maturity was confirmed by the child with the assistance of a parent via a five-point self-assessment of secondary sexual characteristics (Tanner 1962). On average participants scored 3.4 ± 0.4 on The Physical Activity Questionnaire for Older Children (PAQ-C) (0 being inactive, 5 being very active) (Kowalski et al 2004).…”
Section: Participantsmentioning
confidence: 99%